An Efficient Implementation for the Cryptanalysis of Caesar’s Cipher - Asoronye, Gaylord O; Emereonye, Goodluck I; Onyibe, 3Christian O; Agha, Ibiam A (The Melting Pot, 2019)
One of the oldest algorithms for symmetric key cryptography is the Caesar’s cipher. Cryptography or message coding techniques are fundamental data security tools. In order to secure data to be transmitted from source to a particular destination there is need for encrypting the data at source and the decrypting of the encrypted data only made possible at the designated destination. The process of decrypting data known as cryptanalysis proves to be a herculean task if the symmetric key (Caesar’s shift) is not known by the cryptanalyst. In this work, a cryptanalysis of the encryption algorithm using the encryption formula CipherText = PlainText + (Key mod 26) that generates the cipher text and the decryption algorithm using the decrypting formula PlainText = CipherText – (Key mod 26) that returns the cipher text to the original plaintext for the Caesar’s cipher was implemented using file operations in the C programming language. At the instance of inputting a key, it is subjected to modular arithmetic operation with 26 to get a value less or equal to 26, hence transforming the plaintext to a cipher text written into the encrypt.txt file while the decrypted cipher text is written into the decrypt.txt file.